The C. elegans adult neuronal IIS/FOXO transcriptome reveals adult phenotype regulators - Kaletsky, Rachel (Nature, 2015)
Insulin/IGF-1 signaling (IIS) is a critical regulator of an organism’s most important biological decisions, from growth, development, and metabolism to reproduction and longevity. It primarily does so through the activity of the DAF-16/FOXO transcription factor, whose global targets were identified in C. elegans using whole-worm transcriptional analyses more than a decade ago(1). IIS and FOXO also regulate important neuronal and adult behavioral phenotypes, such as the maintenance of memory(2) and axon regeneration(3) with age, in both mammals(4) and C. elegans, but the neuron-specific IIS/FOXO targets that regulate these functions are still unknown. By isolating adult C. elegans neurons for transcriptional profiling, we identified both the wild-type and IIS/FOXO adult neuronal transcriptomes for the first time. IIS/FOXO neuron-specific targets are distinct from canonical IIS/FOXO-regulated longevity and metabolism targets, and are required for IIS/daf-2 mutants’ extended memory. We also discovered that the activity of the forkhead transcription factor FKH-9 in neurons is required for daf-2’s ability to regenerate axons with age, and its activity in non-neuronal tissues is required for daf-2’s long lifespan. Together, neuron-specific and canonical IIS/FOXO-regulated targets enable the coordinated extension of neuronal activities, metabolism, and longevity under low insulin-signaling conditions.